A CASE OF A PRIMIGRAVIDA WITH ANTI-Jra TRANSFUSED INCOMPATIBLE BLOOD AT DELIVERY - Tokusumi, Misuzu; Okamura, Naoko; Takasugi, Yoshiko; Izumi, Yoichiro (Japanese Journal of Transfusion and Cell Therapy, 2012)
A 37-year-old woman underwent blood examination for screening in pregnancy at 10 weeks of her first pregnancy. The irregularity test for antibodies was negative. She experienced premature rupture of membranes and pain, and was hospitalized at 40 weeks. The fetal heart rate fell as low as 70 per minute during labor, and engagement of the head became poor. The baby was delivered with a vacuum extractor. After delivery, massive bleeding continued and the patient developed hemorrhagic shock. However, although blood pressure rapidly recovered following aggressive treatment, bleeding continued. She was given an emergency transfusion of 6 units of RCC and 4 units of FFP, which requires examination for compatibility (saline method). Thereafter, blood samples of transfused and newly ordered RCC were examined for compatibility (PEG-IAT), all of which turned out to be positive. Further examination showed that the patient was Jra-negative. As Jra-antigen is highly common in Japanese, Jra-negative women are often sensitized by Jra-positive fetal RBCs and produce Jra-antibody during pregnancy. In such cases, hemolytic manifestations may be observed after usual transfusion. Fortunately, the patient recovered soon without prolonged hemolytic symptoms or signs. The present case showed that irregular testing for antibodies might be required, even in the later stage of pregnancy as well as in the early stage.